Perceptions for inclusive education in Ecuador - Rojas-Avilés, Héctor (2021)
The aim of this article is to carry out the analysis of the educational inclusion policy in Ecuador and its relationship with the pedagogical actions in force in educational settings. The education systems of the Ecuadorian state, despite being aligned with international inclusion parameters, have not overcome the discrimination gap for people with special educational needs (SEN). This document mainly contributes to innovation in the pedagogical thinking of teachers, for this reason, part of the Warnock report (document that was prepared by the British Education Commission) which revolutionizes the way of thinking of people when revealing that “There are no uneducable children” (Warnock, 1987, p. 15). The methodology used in the structuring of this work is inductive - deductive and is based on bibliographic research. The results of this study reveal shortcomings and difficulties in the educational inclusion of students with SEN, the most relevant problems observed were the conceptual deficiencies around educational inclusion, poor knowledge about an inclusive curriculum and weaknesses in a supposed homogeneity in the classroom. This document briefly presents some perspectives and challenges to promote inclusive thinking but, above all, a thinking open to diversity.